Regions of Domestic Ungulate Grazing according to Strontium Isotope Composition Data in Materials from Novotemirsky and Vorovskaya Yama Ancient Mines (Southern Trans-Urals) - Polina S. Ankusheva; Andrey V. Epimakhov (Археология евразийских степей)
The article presents a comparative description of the strontium isotopic composition in bone remains from the cultural layer of two copper mines in the steppe Trans-Urals. The purpose of the work is to identify possible regions for supplying the Bronze Age miners with meat products. The sample includes 38 measurements of 87Sr/86Sr in the enamel of teeth and bones of cattle, caprines and horses. 20 of them come from materials of the Novotemirsky mine, 18 - from the collection of the Vorovskaya Yama mine. Although the grazing regions of both sites are linked with the Southern Trans-Urals, differences in the organization of animal supplies for these two mines are expected. The ratios of strontium isotopes in most samples from the Novotemirsky mine are similar to the background ones, which suggests that the population of surrounding settlements was involved in the development of the deposit. The data from the Vorovskaya Yama mine sample reflect the formation of a large part of the livestock from more remote areas, up to 100 km east of the mine. The obtained results suggest differences in mining patterns in the Bronze Age in the same region and in deposits with similar geological characteristics.